PSYCHOLOGICAL ASPECTS THAT A FOREIGN LANGUAGE TEACHER SHOULD PAY ATTENTION TO DURING THE EDUCATIONAL PROCESS - Ashurova Shakhzoda Shavkatovna (American Journals, 2023)
A foreign language teacher's conscious perception of the importance of his professional activity requires him to successfully perform a number of professional functions. These functions include teaching, educational, organizational and research functions of a pedagogue.
Keywords: Reveals, intuition, sufficiently, existence, perception, manifested, conceptualization.